MOTIVATION OF STUDENTS TO EXERCISES IN THE PROCESS OF FORMING PROFESSIONAL COMPETENCE OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2010)
The distinctions in motivation for training in physical exercises of the young men and women at the Technology-and-Pedagogics Department of the Krvvyi Rih Pedagogical University have been revealed.
Keywords: professional competence; professional motivation; motivational needs of students